2016
DOI: 10.3389/fpls.2016.01293
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity and Physiological Performance of Portuguese Wild Beet (Beta vulgaris spp. maritima) from Three Contrasting Habitats

Abstract: The establishment of stress resilient sugar beets (Beta vulgaris spp. vulgaris) is an important breeding goal since this cash crop is susceptible to drought and salinity. The genetic diversity in cultivated sugar beets is low and the beet wild relatives are useful genetic resources for tolerance traits. Three wild beet populations (Beta vulgaris spp. maritima) from contrasting environments, Vaiamonte (VMT, dry inland hill), Comporta (CMP, marsh) and Oeiras (OEI, coastland), and one commercial sugar beet (Isell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 54 publications
0
49
0
Order By: Relevance
“…maritima (L.) Arcang.) belongs to the Chenopodiaceae family and is a wild relative of cultivated beets (B. vulgaris) which thrives in salt marshes and seashore cliffs and exhibits high salt-stress tolerance (Ribeiro et al, 2016) (Fig. 3a).…”
Section: Edible Halophytes Native In the Mediterranean Basinmentioning
confidence: 99%
See 1 more Smart Citation
“…maritima (L.) Arcang.) belongs to the Chenopodiaceae family and is a wild relative of cultivated beets (B. vulgaris) which thrives in salt marshes and seashore cliffs and exhibits high salt-stress tolerance (Ribeiro et al, 2016) (Fig. 3a).…”
Section: Edible Halophytes Native In the Mediterranean Basinmentioning
confidence: 99%
“…3a). In a recent study, Ribeiro et al (2016) observed that sea beet populations from contrasting environments showed physiological plasticity and recovered from severe stress conditions (drought and salinity stress), while Skorupa et al (2016) reported that several genes related with carbon fixation, biosynthesis of ribosomes and expansion and formation of cell walls are involved in salt tolerance. The edible parts of the plant are its leaves and leaf stems which are eaten as cooked or raw greens throughout the Mediterranean basin (Turner et al, 2011).…”
Section: Edible Halophytes Native In the Mediterranean Basinmentioning
confidence: 99%
“…belongs to the family of Chenopodiaceae. It grows in salt marshes, exhibits high salt-stress tolerance, and can endure harsh conditions (Ribeiro et al 2016). Its leaves and stem are used as food after cooking or raw greens in different regions (Turner et al 2011).…”
Section: 2mentioning
confidence: 99%
“…In Portugal, phenotyping research targets are focused on both model species and crops, at the molecular/cellular level and at the whole-plant level. However, it is still predominantly low-throughput phenotyping, based for example on leaf gas exchange (Cruz de Carvalho et al, 2011; Ribeiro et al, 2016) or thermography (Costa et al, 2016) and medium-throughput phenotyping utilizing rapid chl a fluorescence induction transients (Silvestre et al, 2014). Portugal lacks a phenotyping network and HTPP infrastructures capable of supporting rapid speed characterization of relevant crop traits (e.g., growth, yield, quality, stress resilience).…”
Section: Plant Phenotyping In the South European Mediterranean Regionmentioning
confidence: 99%